Mendeteksi Ancaman Kecanduan Gadget pada Anak Usia Dini - Siti Winda Adriani; Ismaniar Ismaniar; Lili Dasa Putri (Journal Social and Humaniora, 2024)
This article examines providing information for parents in detecting gadget addiction in young children from the start before young children become addicted to gadgets. This study was motivated by the fact that many aged children have gadget addiction disorders such as sleep disorders, aggressive nature, difficulty understanding learning, hunched body posture, reduced brain growth and development, strange behavior, irritability, and unwillingness to socialize. This study discusses 4 (four) discussions, namely (1) factors causing gadget addiction in early childhood, (2) the threat of gadget addiction in early childhood, (3) how to detect the threat of gadget addiction in early childhood, (4 ) The role of parents in preventing gadget addiction in early childhood. Based on the results of the analysis in this paper, it can be concluded that gadget addiction in early childhood is a serious problem that has various negative impacts. Several factors that cause gadget addiction include inappropriate parenting, neuroscientific factors, gadget technology designs that create dependency, and the influence of the surrounding environment. Parents play a key role in preventing gadget addiction by limiting the time they use gadgets, choosing appropriate applications, monitoring gadget use, and being good role models. Parents also need to detect signs of gadget addiction in their children, including changes in behavior, and physical, emotional, social, and academic performance. With the active role of parents, the negative impact of gadget addiction in young children can be minimized.